Biodegradability of petroleum refinery wastewater in batch reactor - Gasim, H.A. (2010)
Biological treatment was used to determine the biodegradability and treatability of the wastewater generated by petroleum refinery facility. The wastewater generated from different processes stored in a balancing tank prior to treatment with average effluent COD concentration ranged from 712 mg/L to 1597 mg/L during study period. Two treatment strategies were developed and tested for treating the wastewater. The strategies are: (i) to determine the biodegradability and (ii) to treat the wastewater using sequencing batch reactor. Aerobic and anaerobic biodegradability test was found to be effective. The COD in the wastewater was removed more than 90% over a period of 15 days and the experiment ended after 28 days. For sequencing batch reactor (SBR), four sets of reactors (aerobic and anaerobic) were operated continuously in batch mode with continuous operation and monitoring. Wastewater COD was removed on average 91% and 38% for aerobic and anaerobic reactors, respectively over 24 hours cycle. Mixing refinery wastewater with domestic wastewater enhanced the treatment slightly over a long period.